Sudden Infant Death Syndrome Mortality Trends and Socioeconomic Inequalities Worldwide: Evidence from the Global Burden of Disease Study - Ze Tang; Ziwei Wang; Xinbao Wang (Children)
Background: Sudden Infant Death Syndrome (SIDS) remains an important global health concern despite its decline in recent decades. This research assesses the global, regional, and national tendencies in SIDS mortality and DALYs from 1991 to 2021, highlighting the differences across various sociodemographic indexes (SDIs). Methods: Utilizing data from the Global Burden of Disease (GBD) study 2021, SIDS mortality and DALYs were evaluated across different global regions, SDI categories, and age groups. The trends over the study period were determined by conducting estimated annual percentage change (EAPC) analyses. Results: Between 1991 and 2021, the global SIDS mortality rate reduced greatly from 74,782 deaths (58.72 per 100,000 infants) to 30,608 deaths (24.16 per 100,000 infants), showing an EAPC of −3.01%. Similarly, the global DALYs decreased from 6,710,608 to 2,746,174. The biggest decline (EAPC: −5.25%) occurred in the high-SDI regions, whereas the low-SDI regions displayed a minimal decline (EAPC: −2.74%). Infants who were 1–5 months old uniformly had the highest mortality and DALY rates. Gender differences persisted, with larger rates discovered among males. The regional differences remained prominent, with the low-SDI states experiencing a much higher burden. Conclusions: Although there have been remarkable global advancements, great differences in the SIDS burden persist, mainly boosted by socioeconomic unfairness and healthcare access. Improved targeted interventions mitigating these modifiable risks and enhancing healthcare infrastructure in low-SDI regions are the keys to further reducing the global SIDS burden.